2023
DOI: 10.1111/ceo.14259
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve diseases and regeneration: How far are we from the promised land?

Abstract: The retinal ganglion cells (RGCs) are the sole output neurons that connect information from the retina to the brain. Optic neuropathies such as glaucoma, trauma, inflammation, ischemia and hereditary optic neuropathy can cause RGC loss and axon damage, and lead to partial or total loss of vision, which is an irreversible process in mammals. The accurate diagnoses of optic neuropathies are crucial for timely treatments to prevent irrevocable RGCs loss. After severe ON damage in optic neuropathies, promoting RGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 124 publications
0
1
0
Order By: Relevance
“…Researchers have revealed the pathophysiology of these conditions, including factors such as ischemia, inflammation, oxidative stress, and neuronal apoptosis. [ 3 ] For example, studies have shown that hypertension, diabetes, and smoking are associated with an increased risk of nonarteritic anterior ischemic optic neuropathy. [ 4 5 ] Recent studies have also shown an increased risk of optic neuropathy in Alzheimer’s disease and Parkinsonism.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have revealed the pathophysiology of these conditions, including factors such as ischemia, inflammation, oxidative stress, and neuronal apoptosis. [ 3 ] For example, studies have shown that hypertension, diabetes, and smoking are associated with an increased risk of nonarteritic anterior ischemic optic neuropathy. [ 4 5 ] Recent studies have also shown an increased risk of optic neuropathy in Alzheimer’s disease and Parkinsonism.…”
Section: Introductionmentioning
confidence: 99%